Design and Simulation of Oil Palm FFB Loading Machine. Issue 1 (1st June 2022) - Desrial,; Muhammad, K
Abstract: The process of loading the fresh fruit bunches of oil palm to the truck requires a lot of manpower if it is done manually. In fact, either the palm oil plantation or the smallholder palm oil farmer still performs this task manually, so that it can lead to fatigue and can result in injuries for the worker due to heavy workload. The purpose of this research is to design and simulate a machine for lifting the fresh fruit bunches to the truck, so that the activities of lifting the fresh fruit bunches to the truck become easier and can have a bigger working capacity. This research was conducted using a functional and structural design approach consisting of several stages, including: problem identification, design concept formulation, engineering analysis, engineering drawings, material strength analysis, kinematics simulation, power consumption simulation, and digital scale simulation. A simple structure of electric motor-driven bucket elevator was designed to load the fresh fruit bunches on to the truck tailgate. Based on the simulation results, the fresh fruit bunches can be lifted up satisfactorily from the bottom to the top with an elevator mechanism. This elevator is designed with lightweight for easy installation and kept at the tailgate of the truck. The maximum electric power consumption for lifting the fresh fruit bunches was found to be 1466.24 watts with designed loading capacity 23 ton/hour.